Does supplementing laying hen diets with a herb mixture mitigate the negative impacts of excessive inclusion of extruded flaxseed? - Hosseini, Hossein; Esmaeili, Noah; Sepehr, Aref; Zare, Mahyar; Rombenso, Artur; Badierah, Raied; Redwan, Elrashdy M (Animal bioscience, 2023)
OBJECTIVE: This study investigated the effects of extruded flaxseed with and without herbs mixture on egg performance, yolk fatty acids (FAs), lipid components, blood biochemistry, serological enzymes, antioxidants, and immune system of Hy-Line W-36 hens for nine weeks. METHODS: Two hundred forty laying hens were randomly distributed to eight treatments, resulting in six replicates with five hens. Graded levels of dietary extruded flaxseed (0, 90, 180, and 270 g/kg) with and without herbs mixture (24 g/kg: garlic, ginger, green tea, and turmeric 6 g/kg each) were designed as treatments. RESULTS: The two-way analysis of variance indicated that hens fed herbs mixture had a higher value of egg production, yolk high-density lipoprotein (HDL), superoxide dismutase, glutathione peroxidase, and white blood cell and lower contents of yolk cholesterol, glucose, and blood low-density lipoprotein than those fed diets without herb mixtures (p<0.05). The Flx27 (270 g/kg flaxseed) (153.5 g/kg n-3 FAs) and Flx27+H (270 g/kg flaxseed plus 24 g/kg herbs mixture) (150.5 g/kg n-3 FAs) groups were the most promising treatments in terms of yolk n-3 FAs content. In-teraction effect (herbs- flaxseed) for blood cholesterol, HDL, malondialdehyde, glutaredoxin, alanine transaminase, (ALT), aspartate transaminase (AST), haemoglobin and immune parameters was significant (p<0.05). The results showed layers fed herbs mixture (Flx9+H, Flx18+H, and Flx27+H) had a better value of total antibody, immunoglobulin M, immunoglobulin G, ALT, AST, and blood HDL as compared with representative flaxseed levels without herbs. CONCLUSION: High inclusion levels of extruded flaxseed (270 g/kg) without herbs to enrich eggs with n-3 appears to impair the antioxidant system, immunohematological parameters, and sero-logical enzymes. Interestingly, the herbs mixture supplementation corrected those effects. Therefore, feeding layers with flaxseed-rich diets (270 g/kg) and herbs mixture can be a promising strategy to enrich eggs with n-3 FAs.
Keywords: Lipid-lowering Effect; Egg Enrichment; Flaxseed; Herbal Medicine; Cholesterol Level